Model−driven Engineering of Information Systems: 10 years and 1000 versions - Davies, J; Gibbons, J; Welch, J; Crichton, E (2014)
This paper reports upon ten years of experience in the development and application of model-driven technology. The technology in question was inspired by work on formal methods: in particular, by the B toolkit. It was used in the development of a number of information systems, all of which were successfully deployed in real world situations. The paper reports upon three systems: one that informed the design of the technology; one that was used by an internal customer; and one that is currently in use outside the development organisation. It records a number of lessons regarding the application of model-driven techniques: in particular, the importance of completeness or closure, the need for multiple models, and the importance of automatic data migration.